SIMED-New Doc course, a matter of reflection - Stirparo, Giuseppe; Solla, Daniele; Gambolò, Luca; Bellini, Lorenzo; Mantovanelli, Luca; Trapani, Martino; Pregliasco, Fabrizio Ernesto; Sarli, Leopoldo; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Obtaining a degree in medicine in Italy qualifies for the medical profession; this fact has entailed a newly qualified doctor’s remarkable involvement on the medical activities of the National Health Service, especially during the Covid-19 pandemic. It is important to understand the knowledge of the newly qualified doctors and to create specific courses oriented to them. The aim of the study is to evaluate the impact of a peer learning course for the students who attend the last year of medicine school, with the purpose of defining the formal requests to integrate on the course. Methods: A pre and post qualitative research has been carried out on SIMED-NEWDOC course. The course consisted on peer teaching lectures, as lecturers were resident doctors part of SIMED board. At the end of the course it has been submitted a survey to the participants, and data has been analyzed. Results: The students enrolled were 139, the average of the participants was 27% of the registered. A qualitative evaluation questionnaire was submitted, the responses were 32 (86%). Average age was 25. Participants attending the last year of medicine school were 30 (95%). 40% of them declared to have attended at least 5 lessons. Among the course participants, 96% judged the course as very useful. Conclusions: All questionnaire results are useful to reflect on future projects. It is necessary to implement further educational projects to better understand the phenomenon, considering the positive impact that participants declared.